2018
DOI: 10.1007/s10796-017-9821-8
|View full text |Cite
|
Sign up to set email alerts
|

Sharing of Sponsored Advertisements on Social Media: A Uses and Gratifications Perspective

Abstract: Organisations are increasingly utilising social media to advertise to, and interact with, consumers. Sponsored advertisements embedded into targeted users' social media feeds appear less invasive than standalone advertisements but, unlike organic postings, incur financial cost. Given that friends' posts attract most attention, this research employs Uses and Gratifications theory to determine salient motivations for users' intentions to share sponsored advertisements, framed in the tourism context. Survey data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
84
3
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 84 publications
(123 reference statements)
6
84
3
7
Order By: Relevance
“…This indicates that when people seek information and news, an altruistic person is always eager to share such news to help without expecting any recompense in the future. The altruistic behaviour has been well tested and documented in knowledge, information and news sharing studies ( Plume and Slade, 2018 , Ma and Chan, 2014 , Fang and Chiu, 2010 ). For instance, Ma and Chan (2014) revealed that altruism is positively associated with the voluntary gathering and dissemination of information, suggesting that users of social media would assist without expecting remuneration.…”
Section: Developing the Research Model And Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that when people seek information and news, an altruistic person is always eager to share such news to help without expecting any recompense in the future. The altruistic behaviour has been well tested and documented in knowledge, information and news sharing studies ( Plume and Slade, 2018 , Ma and Chan, 2014 , Fang and Chiu, 2010 ). For instance, Ma and Chan (2014) revealed that altruism is positively associated with the voluntary gathering and dissemination of information, suggesting that users of social media would assist without expecting remuneration.…”
Section: Developing the Research Model And Hypothesesmentioning
confidence: 99%
“…Altruistic behaviour occurs when individuals share with others without thinking of any reward. Relating this to news sharing, altruism could be described as the act of disseminating news and information without expecting a reward for such an act ( Plume & Slade, 2018 ). An altruistic person constantly has the mind to serve others.…”
Section: Developing the Research Model And Hypothesesmentioning
confidence: 99%
“…The present study is based on Uses and Gratifications Theory and Theory of Reasoned Action to understand the interplay between motives, trust on social media retailers and attitude towards social media marketing. Uses and Gratifications Theory is considered as one of the most prominent and popular theories to understand underlying consumers' motives and their subsequent impact on attitudinal and behavioral outcomes (Plume & Slade, 2018). Originally, UGT was applied to study the media users' interest in the traditional forms of media like newspapers, television, radio, and telephone but now its applicability has also been expanded to other areas of research (Corkindale, Ram, & Chen, 2018;Thongsri, Shen, Bao, & Alharbi, 2018).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The main purpose of Uses and Gratifications Theory is to explain the reasons on the basis of which individuals choose a particular medium over other alternative media (Dolan, Conduit, Fahy, & Goodman, 2016) . It is considered as a well-known and highly valid theory because its principles are generally accepted and can be applied in many situations (Liu, North, & Li, 2017;Plume & Slade, 2018). UGT is a comprehensive framework that identifies consumers' motivations and has evolved over the years (Hossain, 2019;Mishra, 2019;Zong, Yang, & Bao, 2019).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Notably, information sharing was found to have a negative effect, while selfexpression had no significant effect. Results also determined that there were no significant differences in motivations between males and females (Plume and Slade 2018).…”
mentioning
confidence: 94%